Retrospective database study on risk factors for diabetic retinopathy and diabetic kidney disease in Japanese patients with diabetes mellitus - Kota Yamada; Mitsuru Ohsugi; Yuichiro Ito; Hiroki Uchida; Takumi Lee; Kohjiro Ueki (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction This study aimed to investigate the risk factors for diabetic retinopathy (DR) and diabetic kidney disease (DKD) in Japanese patients with diabetes mellitus (DM). Identifying these factors could provide insights into the shared and distinct mechanisms contributing to these complications in the diabetic population. Materials and Methods We conducted a retrospective analysis using the J‐DREAMS (Japan Diabetes compREhensive database project based on an Advanced electronic Medical record System) database, which is directly linked to electronic medical records. The study included Japanese people aged 18 years and older with diabetes, who were registered at a referral center between December 1, 2015, and March 31, 2021, and had simultaneous measurements of serum creatinine and hemoglobin A1c (HbA1c). The presence or absence of DR and DKD was determined for 8,794 and 8,770 patients, respectively. Multivariable logistic regression analyses were used to identify risk factors, considering patient characteristics, comorbid conditions, and laboratory data as explanatory variables. Results Common risk factors for both DR and DKD included hypertension, anemia, diabetic neuropathy, cerebrovascular disease, chronic heart failure, low serum albumin levels, and elevated HbA1c. The contributions of age, duration of DM, and body mass index (BMI) differed between the DR and DKD groups. Conclusions In addition to poor glycemic control and hypertension, anemia, low serum albumin, cerebrovascular disease, and heart failure were identified as independent common risk factors for DR and DKD, suggesting the existence of cardio‐renal anemia syndrome in patients with DM.